PENGARUH IMPLEMENTASI KEBIJAKAN PEMEKARAN WILAYAH TERHADAP PENINGKATAN PELAYANAN PUBLIK DI DESA APENG SEMBEKA KECAMATAN SANGKUB KABUPATEN BOLAANG MONGONDOW UTARA - MAKASILI, VIRLI; LENGKONG, FLORENCE DAICY; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2020)
The implementation of regional expansion policies that have been carried out through severalstages that are mature, planned and systematic greatly affect the quality of life of the community,both in the aspects of development, public services and in improving the welfare of the communityin Apeng Sembeka Village, Sangkub District, Bolaang Mongondow Utara Regency. This study usesquantitative research methods that try to answer the magnitude of the effect of the variableimplementation of regional expansion policies towards the variable improvement of publicservices.Data collection is done through careful observation, questionnaires in a detailed context, indepthinterviews, and analysis results. The results of the simple linear regression analysis testshowed the influence of the variable implementation of regional expansion policies on theimprovement of public services had a positive and significant effect, and through correlationanalysis showed that there was a relationship between the variable implementation of the regionalexpansion policies on increasing public services by 62.7% while the rest amounted to 37.4% isinfluenced by other factors.Keywords :Policy Implementation, Area Expantion, Public Service